2020
DOI: 10.31616/asj.2019.0236
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Bodyweight Reduction before Lumbar Fusion Surgery Increased Postoperative Complications

Abstract: To determine the effects of massive weight loss on perioperative complications after lumbar fusion surgery (LFS). Overview of Literature: Patients who are obese are more likely to experience low back pain, which would require LFS. Nonetheless, they have a higher risk of perioperative complication development compared with individuals who are not obese. Methods: Patients who underwent LFS at hospitals that participated in the National Surgical Quality Improvement Program database within the United States betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The extent and speed of weight loss may be another consideration when counseling patients before spine surgery. A >10% loss in body weight over 6 months before spine surgery has been shown to be associated with worse clinical outcomes such as DVT, increased incidence of blood transfusions, higher organ/space surgical site infections, and increased hospital length of stay 21. Therefore, a history of rapid weight loss before spine surgery in patients who have undergone BS could predispose these patients to a higher risk of readmission, reoperation, and all-cause complications.…”
Section: Discussionmentioning
confidence: 99%
“…The extent and speed of weight loss may be another consideration when counseling patients before spine surgery. A >10% loss in body weight over 6 months before spine surgery has been shown to be associated with worse clinical outcomes such as DVT, increased incidence of blood transfusions, higher organ/space surgical site infections, and increased hospital length of stay 21. Therefore, a history of rapid weight loss before spine surgery in patients who have undergone BS could predispose these patients to a higher risk of readmission, reoperation, and all-cause complications.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our sensitivity analysis results, we feel that while our model did not specifically capture a patient with a BMI more than 35, such a patient would benefit even more from preoperative bariatric surgery prior to elective outpatient surgery. Jensen et al 20 reported that patients with a history of bariatric surgery fared worse than those without while Rudy et al 21 have recently published work demonstrating that rapid weight loss within 6 months of elective lumbar surgery led to increased postoperative complications. However, the optimal waiting period following bariatric surgery and prior to elective lumbar surgery remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among patient demographics, comorbidities and obesity are known to be significant risk factors for increasing perioperative blood loss. [12][13][14][15][16][17][18] Therefore, in this study, various factors such as obesity, use of medical drugs, and comorbidities were also evaluated.…”
Section: Introductionmentioning
confidence: 99%